Analysis of Ca2+ and Fe2+ Ions in Ngade Water and Tolire Lake Water Ternate, North Maluku - Fadlan Muin; Muhammad Amin; Saras Wati Banapon (TECHNO: JURNAL PENELITIAN, 2022)
This study aims to obtain optimal and valid conditions for the analysis of inorganic ions Ca2+ and heavy metal Fe2+ and the comparison between inorganic ions Ca2+ and heavy metal ions Fe2+ contained in the water of Lake Ngade and Lake Tolire, using ion chromatography and UV-Vis spectrophotometry. This type of research is experimental laboratory. Based on the results of the research, the concentrations obtained from Ca2+ ions and Ca2+ ions are for the highest concentration of Ca2+ ions in Lake Ngade water at 1.259 ppm, Big Tolire Lake water at 3.410 ppm and Small Tolire Lake water at 6.154 ppm. Meanwhile, the highest concentration of Fe2+ ions is in Lake Ngade water at 5.606 ppm, Big Tolire Lake water at 5.500 ppm, and Small Tolire Lake water at 5.379 ppm.